CORRUPTION, GOVERNMENT’S ECONOM-IC PERFORMANCE AND INSTITUTIONAL TRUST IN THE MENA REGION - KOUBAA, Salah (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: Countries in the MENA region are perceived as highly corrupt. They are struggling to achieve clear results against corruption. Unfortunately, no country has reached a significant improvement on the Corruption Perceptions Index (CPI) published by Transparency International in 2021. The United Arab Emirates and Qatar are the top performers in the Region. The former was ranked 69 out of 100, the latter 63 out of 100. Libya (17/100), Yemen (16/100), and Syria (13/100) awfully damaged by the war are the worst. The state-of-the-art impacts trust at the national level and the performance of public institutions as well. Aim: This paper aims to study the relationship between corruption and trust, and its impact on public economic performance in the MENA region. It is based on the data provided by Arabbarometer, 2018-2019. Our sample includes 8215 individuals located in 12 countries in that region. To test all our hypotheses simultaneously, we have used the structural equation modeling method with SmartPLS software. The latent variable of the research model – corruption, fighting corruption, and economic performance of the government- all of them are used as a reflective measurement. However, trust is included in the model as a formative measurement. Results: The findings show that trust in public institutions, measured by a formative scale, is negatively impacted by the level of corruption (-0,36). It also depends on the efforts made by the state to fight corruption in public agencies and institutions (0,37). Trust is one of the most important components of social capital. The performance of public policies is highly correlated to the level of trust between public administration and individuals. The government’s economic performance depends on the level of that trust (0,341), the efforts made to fight corruption (0,173), and public corruption (-230). All hypotheses are significant at 1%.